2012
DOI: 10.1590/s0100-879x2012007500016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous hydrogen sulfide inhibition on structural and functional renal disturbances induced by gentamicin

Abstract: Animal models of gentamicin nephrotoxicity present acute tubular necrosis associated with inflammation, which can contribute to intensify the renal damage. Hydrogen sulfide (H2S) is a signaling molecule involved in inflammation. We evaluated the effect of DL-propargylglycine (PAG), an inhibitor of endogenous H2S formation, on the renal damage induced by gentamicin. Male Wistar rats (N = 8) were injected with 40 mg/kg gentamicin (im) twice a day for 9 days, some of them also received PAG (N = 8, 10 mg·kg−1·day−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Although most of the literature supports the notion that hydrogen sulfide protects against oxidative stress and thus generally also against renal disease (Koning et al , ; Lobb et al , ), some recent studies suggest that treatment with the CSE inhibitor propargylglycine (PAG) inhibits endogenous H 2 S production and increases antioxidant enzyme expression while significantly improving renal function reducing renal damage, fibrosis, and inflammation. Another study demonstrated that PAG‐treated animals exhibited significantly improved renal function and decreased renal necrosis as well as decreased ROS production, oxidative stress, and caspase activation following gentamicin treatment (Francescato et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the literature supports the notion that hydrogen sulfide protects against oxidative stress and thus generally also against renal disease (Koning et al , ; Lobb et al , ), some recent studies suggest that treatment with the CSE inhibitor propargylglycine (PAG) inhibits endogenous H 2 S production and increases antioxidant enzyme expression while significantly improving renal function reducing renal damage, fibrosis, and inflammation. Another study demonstrated that PAG‐treated animals exhibited significantly improved renal function and decreased renal necrosis as well as decreased ROS production, oxidative stress, and caspase activation following gentamicin treatment (Francescato et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous present studies in animals and humans have shown H 2 S possess important physiological and pathophysiologic functions, such as the regulation of blood pressure [25], inflammation [26], renal damage [27], neurodegenerative diseases [28,29,] and metabolic disorders, including obesity and diabetes [30]. Liu et al found that H 2 S can improve wound healing by restoring endothelial progenitor cell functions and activation of Ang-1 in type 2 diabetic mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the adverse impact of relative H2S deficiency in models of renal disease described so far, in rat models of cisplatin, adriamycin and gentamicin-induced nephrotoxicity endogenous H2S has been reported to aggravate renal damage [93][94][95][96]. However, this assumption was based on the finding that PAG reduced renal damage caused by injection of these nephrotoxic substances.…”
Section: H2s In the Onset And Progression Of Renal Diseasementioning
confidence: 92%